2021
DOI: 10.1016/j.heliyon.2021.e06937
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and physico-chemical quality of household drinking water in Kisii Town, Kisii County, Kenya

Abstract: Water is a basic human need which is required in many operations especially in households. However, this essential commodity in most cases does not meet the generally accepted safety standards. The study was designed to investigate the physico-chemical and bacteriological quality of drinking water used in households in Kisii town, Kenya. Analytical cross-sectional study was conducted to obtain information concerning household drinking water quality and safety. Stratified random sampling was used to obtain 422 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
10
14
0
Order By: Relevance
“…Our finding also indicated that E. coli were detected in 47.1% of tap water samples from the collection point which was consistent with 50% of tap water samples having E. coli in North Gondar, Ethiopia (Admassu et al, 2000) and 53% tap water contamination prevalence reported in Africa (Bain et al, 2014) but it was higher than 33% of E. coli contamination reported from Addis Ababa city (Crampton, 2005), 37% of tap water samples from Nekemete Town, Oromia zone, Ethiopia (Duressa et al, 2019) and 17.5% of E. Coli contamination of tap water sample from Kisii Town, Kenya (Ondieki et al, 2021). E. coli were also detected in 48.8% of household water storage containers for consumption which was higher compared to E. coli contamination of 37% tap water samples collected at the point of use in Addis Ababa city (Crampton, 2005) and 4.58% of water samples from a storage container in South Darfur, Sudan (Abdelrahman, 2011).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our finding also indicated that E. coli were detected in 47.1% of tap water samples from the collection point which was consistent with 50% of tap water samples having E. coli in North Gondar, Ethiopia (Admassu et al, 2000) and 53% tap water contamination prevalence reported in Africa (Bain et al, 2014) but it was higher than 33% of E. coli contamination reported from Addis Ababa city (Crampton, 2005), 37% of tap water samples from Nekemete Town, Oromia zone, Ethiopia (Duressa et al, 2019) and 17.5% of E. Coli contamination of tap water sample from Kisii Town, Kenya (Ondieki et al, 2021). E. coli were also detected in 48.8% of household water storage containers for consumption which was higher compared to E. coli contamination of 37% tap water samples collected at the point of use in Addis Ababa city (Crampton, 2005) and 4.58% of water samples from a storage container in South Darfur, Sudan (Abdelrahman, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, total coliforms were detected in 65.7%, of tap water samples from collection points which were lower than TC detected in all tap water samples in Nekemte Town, Oromia, Ethiopia (Duressa et al, 2019), 39.6% of tap water samples from Kisii Town, Kenya (Ondieki et al, 2021), 55.3% of tap water samples in Dharan Municipality, Nepal (Narayan Dutt et al, 2016), 36.3% of tap water samples in northern India and 36.4% of tap water samples in Maringa city, Brazil (Zamberlan, 2008). About 98.8% of water samples collected from household storage container for consumption was positive for TC.…”
Section: Discussionmentioning
confidence: 82%
“…The comparisons in this and subsequent sections are based on findings published earlier by Ondieki et al (2021). According to the findings, out of the tested 422 water samples, 167 (39.6%) were contaminated with total coli forms while 74 (17.5%) had E. coli.…”
Section: Relationship Between Socio-demographic Characteristics and F...mentioning
confidence: 90%
“…The questionnaires were first tested in Menyinkwa area (a different nearby location) in April 2019 to gauge their suitability after which required changes were made before the real study was rolled out between May-October 2019. Table 1 below shows results of bacteriological quality of drinking water in the studied households as reported earlier by Ondieki et al (2021). These results were generated from tested water samples that were simultaneously collected with the questionnaires.…”
Section: Data Analysis and Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation